2007
DOI: 10.2514/1.24662
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal Imploding Detonation Wave Initiator for Pulse Detonation Engines

Abstract: Imploding toroidal detonation waves were used to initiate detonations in propane-air and ethylene-air mixtures inside of a tube. The imploding wave was generated by an initiator consisting of an array of channels filled with acetylene-oxygen gas and ignited with a single spark. The initiator was designed as a low-drag initiator tube for use with pulse detonation engines. To detonate hydrocarbon-air mixtures, the initiator was overfilled so that some acetylene oxygen spilled into the tube. The overfill amount r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Increasing the diameter of the detonation tube to the values used by Li and Kailasanath [22] could enhance the initiation process by allowing the imploding shock wave to achieve higher values of compression during the implosion process. However, an increased tube diameter would also reduce the amount of confinement, moving potential reflecting surfaces away from the implosion focus, which has been shown to be detrimental to the success of the implosion process [2]. Thus, it is not clear what net effect changing the diameter would have on the initiation process.…”
Section: Summary Plots Of the Incident Shock Tube Mach Numbermentioning
confidence: 91%
See 4 more Smart Citations
“…Increasing the diameter of the detonation tube to the values used by Li and Kailasanath [22] could enhance the initiation process by allowing the imploding shock wave to achieve higher values of compression during the implosion process. However, an increased tube diameter would also reduce the amount of confinement, moving potential reflecting surfaces away from the implosion focus, which has been shown to be detrimental to the success of the implosion process [2]. Thus, it is not clear what net effect changing the diameter would have on the initiation process.…”
Section: Summary Plots Of the Incident Shock Tube Mach Numbermentioning
confidence: 91%
“…The current study is intended to serve as an extension of earlier initiation work using imploding detonation waves [2,17] and is motivated by recent numerical simulations that proposed to further refine this initiation technique through use of an imploding toroidal shock wave (instead of an imploding detonation wave) driven by jets of air or fuel. Li and Kailasanath [22] found that detonations could be initiated in a 14-cm-diam tube filled with stoichiometric ethylene-air using an imploding shock wave created from the injection of a converging annular jet of fuel or air at the outer diameter of the tube.…”
Section: Previous Research On Imploding Wavesmentioning
confidence: 99%
See 3 more Smart Citations